2013
DOI: 10.3109/02770903.2013.828303
|View full text |Cite
|
Sign up to set email alerts
|

Parent report and electronic medical record agreement on asthma education provided and children’s tobacco smoke exposure

Abstract: We found low concordance between the parent's report and the electronic medical record for smoke exposure and asthma education provided. Un- or under-documented smoke exposure and health education have the potential to affect continuity of care for pediatric patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Our findings were similar to those of other studies in different settings. A study of children with asthma recruited from health departments and asthma clinics 26 found poor agreement across all clinics between EHR documentation and parent report, although agreement was higher within asthma specialty clinics (k 0.410 compared with 0.205). In 1 study of infants and young children in a primary care clinic, reported TSE based on 1 question about exposure to passive TSE was 13% compared with 55% with cotinine-verified exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to those of other studies in different settings. A study of children with asthma recruited from health departments and asthma clinics 26 found poor agreement across all clinics between EHR documentation and parent report, although agreement was higher within asthma specialty clinics (k 0.410 compared with 0.205). In 1 study of infants and young children in a primary care clinic, reported TSE based on 1 question about exposure to passive TSE was 13% compared with 55% with cotinine-verified exposure.…”
Section: Discussionmentioning
confidence: 99%